Handouts For Undergraduate Teaching : Practical Tips - Soudarssanane M.B; Singh M.C; Rotti S; Srinivasa D.K (Wolters Kluwer Medknow Publications, 1993)
Handouts form an important teaching aid in lectures. At the Department of preventive and social Medicine, JIPMER, over the last 4 years, handouts on selected topics have been developed and used in the training of medical undergraduates. Based on the experience gained thereby, practical tips in the development of handouts have been given.